Cortical microstructure is associated with tau burden and predicts cognitive decline and clinical progression in healthy older adults. (1st February 2022) - Rodriguez‐Vieitez, Elena; Montal, Victor; Sepulcre, Jorge; Lois, Cristina; Hanseeuw, Bernard; Vilaplana, Eduard; Schultz, Aaron P.; Properzi, Michael J; Scott, Matthew R.; Amariglio, Rebecca E.; Papp, Kate V.; Marshall, Gad A; et al.
Abstract: Background: Non‐invasive biomarkers of neuronal injury may be useful to detect cognitively‐normal individuals at risk of developing AD. A recent diffusion‐weighted imaging (DWI) method has allowed to assess microstructural properties of the brain's grey matter by means of cortical mean diffusivity (cMD) (Montal et al. Alz&Dem 14(3):340, 2018). Increased cMD is thought to reflect early neuronal injury that may precede macrostructural neurodegeneration. Here, we aimed to investigate the association of cMD with in vivo amyloid‐β and tau pathology in cognitively‐normal individuals, and to determine whether cMD can predict cognitive decline and clinical progression. Method: 196 cognitively‐normal participants from the Harvard Aging Brain Study (72.5±9.4 years; Table 1) underwent concurrent DWI, T1w‐MRI, 11 C‐PIB‐PET, 18 F‐flortaucipir (FTP)‐PET imaging and cognitive assessments at baseline. PIB‐PET was quantified using non‐PVC‐corrected Logan‐DVR, and FTP‐PET using PVC‐corrected SUVr; PET data were normalized to cerebellar grey‐matter. Longitudinal measures of Preclinical Alzheimer Cognitive Composite (PACC5) were available for n=186 individuals over a 3.72±1.96 yr follow‐up interval. Surface‐based image analysis (FreeSurfer 6.0) was performed to investigate vertex‐wise relationships between cMD and global amyloid‐β (PIB‐FLR), as well as tau (entorhinal, inferior‐temporal FTP). We assessed whether regional cMD predicted longitudinal PACC5 using linear mixed‐effects models, and progression to MCI using Cox proportional‐hazards regression. Result: Entorhinal and inferior‐temporal tau, but not amyloid‐β, were associated with increases in surface‐based cMD in AD‐signature clusters (Fig. 1A); illustrated for middle‐temporal gyrus cMD (Fig. 1B). Correcting for demographics and baseline PACC5, increased cMD within AD‐signature regions‐of‐interest predicted the rate of subsequent cognitive decline, which remained significant after correcting for PIB‐FLR and regional cortical thickness; there was a synergistic interaction between cMD and PIB‐FLR on the slope of PACC5 decline (Fig. 2). From n=163 participants with clinical follow‐up data, 11/163 (6.7%) converted to MCI within 3.3±1.5 years. Dichotomized regional cMD (top‐tertile group being "high cMD") predicted conversion to MCI, illustrated for the middle‐temporal gyrus, hazard ratio HR[95% CI] = 5.21 [1.14‐23.75], p=0.03, corrected by age, sex and education (Fig. 3). Conclusion: cMD is a promising technique to quantify cortical microstructural changes possibly related to tau‐induced neuronal injury. Its ability to predict short‐term cognitive decline and clinical progression suggests utility in clinical trials.